Physostigmine modulation of acetylcholine currents in COS cells transfected with mouse muscle nicotinic receptor - Svobodová, Lucie; Krůšek, Jan; Hendrych, Tomáš; Vyskočil, František (Neuroscience letters, 2006)
Physostigmine (Phy), a reversible inhibitor of acetylcholine (ACh) esterase (AChE), may also act as a low potency agonist and a modulator of the nicotinic receptor. The actions of Phy on mouse muscle nicotinic receptors in the COS-7 cell line were studied by the patch-clamp technique. Currents were recorded in the whole-cell mode 3-7 days after cell transfection by plasmids coding alphabetagammadelta combination of receptor subunits. The application of ACh to cells clamped at -10 mV produced inward currents which displayed desensitization. The application of Phy in concentrations up to 1 x 10(-3) M did not give reliable specific whole-cell membrane responses. The application of Phy in concentrations of 10(-6)-10(-4) M together with ACh modulated the amplitude; accelerated desensitization of currents induced by ACh and increased the final extent of desensitization in a concentration-dependent manner. This finding is in contrast to the suppression and slowing down of desensitization by Phy and 1-methyl-galanthamine observed in Torpedo receptors.
Keywords: Dose-Response Relationship, Drug; synergismus léků; Receptors, Nicotinic; nervosvalové spojení; Physostigmine; vztah mezi dávkou a účinkem léčiva; buněčná membrána; nikotinové receptory; myši; acetylcholin; Drug Synergism; cholinesterasové inhibitory; Cell Membrane; Mice; Patch-Clamp Techniques; genetické vektory; Genetic Vectors; Animals; Financing, Organized; Cholinesterase Inhibitors; Synaptic Transmission; fysostigmin; metoda terčíkového zámku; zvířata; kosterní svaly; Neuromuscular Junction; COS Cells; Muscle, Skeletal; COS buňky; iontové kanály; Chlorocebus aethiops; financování organizované; nervový přenos; Acetylcholine; Ion Channels; membránové potenciály; Transfection; Cercopithecus aethiops; transfekce; Membrane Potentials